Choosing from the Reform Menu Card: Individual Determinants of Labour Market Policy Preferences - Tanja Hennighausen; Ivo Bischoff; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This contribution empirically explores the drivers of labour market reform acceptance for the individual level in Germany. For that purpose we make use of the representative German General Social Survey (ALLBUS). This survey offers data to which extent individuals support benefit cuts, longer working years, cutting subsidies to declining industries, phasing out of employment programmes or a liberalisation of employment protection. Our theoretical considerations suggest that self-interest, information, fairness judgements, economic beliefs and other individual factors such as socialisation under the communist regime in the former German Democratic Republic drive individual reform preferences. Our empirical results support this notion: While we find self-interest to be an important driving force, our results show that a number of factors well beyond the narrow scope of self-interest strongly shape individual reform preferences.
Keywords: A13; J48; D63; C42; 330; labour market reform; economic beliefs; fairness preferences; ALLBUS; Arbeitsmarktpolitik; Reform; Hartz-Reform; Meinung; Soziale Werte; Deutschland